The Neurobiology of Olfaction - Menini, Anna (Frontiers in neuroscience, 2010)
A comprehensive overview of the current status of knowledge and research on olfaction, this volume takes an interdisciplinary approach to include content from genetics to behavior and from nematodes to humans. It offers chapters on recent discoveries in odor coding from the olfactory epithelium to the cortical centers, and in neurogenesis in the olfactory epithelium and the olfactory bulb. Written by a top researcher in the field, each subject-specific chapter provides an extensive list of reviews and original articles for students and scientists interested in further reading.